Plan de negocios para La creación de una empresa decoradora de autos clásicos (Tuning), cantón La Maná, año 2013 - Guaranda Shigui, Verónica Aracely (2015)
Currently customizing vehicles through tuning is a trend that is increasing both in the canton La Mana as in various cities of our country, in the canton of La Maná market there is still dedicated specifically to the identification of their vehicles through tuning, it is making it a booming market. Considering these points is intended to solve a latent need for users, developing a business plan for the creation of a company decorator classic cars tuning service in Canton La Mana, and thus cater to this demand, the desires and needs that have them. The company will be called "CRAZY FIRE", its location will be in the Carlos Lozada and Amazonas Avenue. The advertising is done through radio, television and social networks. The market research developed, it was established that there is an unmet need in relation to the existing offer. In the technical study the location, size, infrastructure according to the needs of the company, distribution of work areas, services, costs and personnel requirements and raw materials is established. The investment required for the project in the financial statements, income statements, cash flow underlying for financial evaluation also points out, showing the benefit / cost and profitability that will build the project. An investment of $ 51,355.58, the same that will be financed by 70% against a claim which it held at the financial institution and the remaining 30% will be draped with own contributions shall require the credit obtained will be with an interest 14% 5-year term. NPV equals $ 94,964.14....